Association Between Hormonal Contraception and Blood Glucose Level Among Women of Childbearing Age in Sangkrah Community Health Center, Surakarta - Sabania, Brillian Ferika; Murti, Bhisma; Hanim, Diffah (Indonesian Journal of Medicine, 2016)
Background: Hormonal contraceptive contains estrogen and progesterone hormones. These hormones are hypothesized to affect blood glucose level. This study aimed to determine the association between hormonal contraception and blood glucose level among childbearing aged women.Subjects and Method: This was an analytic observational study with cross-sectional design. The study subjects were childbearing aged women who used and did not use hormonal contraceptive in Sangkrah community health center, Surakarta. A total sample of 47 people consisting of 32 hormonal contraceptive users and 15 non users were selected for study by fixed exposure sampling. The data were collected by questionnaire, interview, anthropometric measurement, and direct measurement of blood glucose level. The data were analyzed using a multiple linear regression with SPSS for Windows.Results: Women of childbearing age who used hormonal contraceptive had an average blood glucose 26 mg / dL higher than the non-users of hormonal contraceptive (b = 26.18; 95% CI 15.03 to 37.33; p <0.001). These estimates had controlled for the effect of confounding variables (i.e. Body Mass Index and diabetes mellitus risk factors).Conclusion:Â There is a positive and statistically significant association between the use of hormonal contraceptive and blood glucose level among women of childbearing age.Keywords: hormonal contraception, blood glucose level.Correspondence:Â Brillian Ferika Sabania. Faculty of Medicine, Sebelas Maret University, Surakarta.Indonesian Journal of Medicine (2016), 1(1): 1-11https://doi.org/10.26911/theijmed.2016.01.01.01